Bibliographie - Hirsch, H.
286-364: Assyriologie; 365-395: Kuyunjik-Sammlung (R. Borger); 396-412: Mesopotamien; 413-431: Kleinasien (H. M. Kümmel); 432-435: Südarabien (W. M. Müller); 436-487: Ägypten (G. Vittmann)